Pengembangan Aplikasi Belanja Pintar Berbasis Linked List dengan Fitur Checklist dan Prioritas - Juliana Gloria Sipayung; Dinda Syafitri; Muhammad Farrel Evan Yuri; Raja Ansel Haratama Sihombing (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
Shopping activities in daily life require proper recording to stay organized and efficient. Manual recording using paper or simple applications often creates difficulties when updates are needed, such as adding new items, removing purchased goods, or rearranging priorities. This study develops a web-based Smart Grocery List application utilizing the linked list data structure. The research stages were carried out independently, starting from idea planning, application design, system implementation, and testing to ensure proper functionality. The application provides core features such as item addition, item deletion, and categorization into immediate and later groups. The results show that the system works according to user needs, supports more systematic shopping list management, and has the potential to be developed further as a practical digital solution.